The Parthenon Marbles as icons of nationalism in nineteenth‐century Britain. Issue 4 (27th August 2013) - Rose‐Greenland, Fiona
Abstract: Theories of nationalism place native culture at the core of national self‐fashioning. What explains a state's adoption of foreign objects to sustain national identity? In this paper, I argue that the incorporation of the Parthenon Marbles into British public life is an early example of supranational nationalism. The nineteenth‐century 'art race' was a competitive field in which European nation‐states vied for prestige. Of the thousands of art trophies that were brought to Britain from Mediterranean and North African countries, the Parthenon Marbles were uniquely iconicised. Using data from period newspapers and official documents, I assert that this was because they were assiduously presented as pre national by British authorities. In this way, they belonged simultaneously to no nation, to every nation, and to Britain. The case demonstrates the emergence of a particular form of national distinctiveness that transcended the smallness of particularity and rose to the level of universal civilisation.